Korupsi dan Pelayanan Publik Sektor Kesehatan di Kabupaten Kutai Kartanegara - Lutfi Wahyudi (Jurnal Ilmu Pemerintahan, 2024)
This article discusses corruption and public services in the health sector in Kutai Kartanegara district during Rita Widyasari's leadership period (2010-2015 and 2016-2020) with the aim of analyzing and explaining the relationship between these two variables. Using a qualitative descriptive approach, the findings were obtained that the corruption that occurred in Kutai Kartanegara district was not closely related to public services in the health sector. This can be seen from several health indicators in this study, namely life expectancy, maternal mortality and infant mortality which tend to experience positive developments. The average life expectancy increased by 0.67% from 71.48 years in the first period to 71.96 years in the second period. The average maternal mortality rate decreased by 3.18% from 220 to 213 in the second period. The infant mortality rate decreased by 1.79% from 13.39 to 13.15 in the second period.